Literature riview: Ethnoparmacognosy, chemical content, and pharmacological activity of Kirinyuh (chromolaena odorata L.) leaves - Wulandari, Indri; Wirasutisna, Komar R; Mariani, Ria; Wibowo, Diki Prayugo (Journal of Midwifery and Nursing, 2024)
Chromolaena odorata L. is a foliaceous plant that has its origins in the Americas and has since proliferated across Indonesia, Africa, and the Pacific region. Chromolaena odorata leaf is a botanical specimen that possesses alkaloids, flavonoids, tannins, saponins, and steroids, which are known for their therapeutic properties. The approach used in this article review involves conducting online literature studies. The research data consists of publications obtained from respected journal sites such as Google Scholar, PubMed, Science Direct, and Research Gate.The articles were chosen from publications that covered the time frame from 2013 and 2023. The purpose of this article is to present detailed information regarding the ethno-pharmacognosy, chemical composition, and pharmacological activity of Kirinyuh leaves (Chromomolaena odorata L.).